2001
DOI: 10.1046/j.1523-1739.2001.99023.x
|View full text |Cite
|
Sign up to set email alerts
|

Songbird Abundance and Avian Nest Survival Rates in Forests Fragmented by Different Silvicultural Treatments

Abstract: Concerns over declining songbird populations have led to investigations of the effects of various silvicultural practices on breeding songbirds. Few studies published, however, have examined both songbird populations and avian nest success among harvesting treatments, particularly in forested landscapes. We conducted a study in the Monongahela National Forest of West Virginia during the summers of 1993 to 1996 to compare breeding-bird abundance and daily nest survival rates among different sivicultural treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 27 publications
3
49
0
Order By: Relevance
“…During the extended response years, nests in this guild were highly successful in the combination thin + burn treatment, but were no different from control in the individual thin and burn treatments. The individual treatments having no significant effect on this guild is consistent with previous results [38,40,41], but the significant increase in nesting success in the combination thin + burn treatment is a novel result.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…During the extended response years, nests in this guild were highly successful in the combination thin + burn treatment, but were no different from control in the individual thin and burn treatments. The individual treatments having no significant effect on this guild is consistent with previous results [38,40,41], but the significant increase in nesting success in the combination thin + burn treatment is a novel result.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, nest success did not differ for understory nesting species between two-age thinned treatments and control forest in West Virginia [40], or for birds in either nesting guild in thinned forests in southern Illinois [41]. Barber et al [42] found that nesting success in some shrub nesting species decreased in thinned pine plantations in relation to previous other published studies, whereas Bourque and Villard [43] found that selective cutting lowered Ovenbird (Seiurus aurocapillus) nesting success.…”
Section: Overview Of Effects Of Burns and Thinning On Avian Nest Survmentioning
confidence: 77%
“…Agestam et al (2003); 2, Baker and Lacki (1997); 3, Beese and Bryant (1999); 4, Brais et al (2004); 5, Chambers et al (1999); 6, 7, Chan-McLeod and Bunnell (2002); 8, Dahlberg et al (2001); 9, Duguay et al (2000); 10, Duguay et al (2001);11, Felix et al (2004); 12, Hannerz and Hånell (1993); 13, Hannerz and Hånell (1997); 14, Harpole and Haas (1999); 15, Harrison and Kilgo (2004); 16, Holgen and Hånell (2000); 17, Hood (2001); 18, Hyvärinen et al (2005); 19, Jalonen and Vanha-Majamaa (2001); 20, King and DeGraaf (2000); 21, Koivula (2002); 22, Lance and Phinney (2001); 23, Lazaruk et al (2005); 24, Lemieux and Lindgren (2004); 25, Lesak et al (2004); 26, Lindo and Visser (2004);27, MacKenzie and Steventon (1996); 28, Merrill et al (1998);29, Nilsson et al (2002);30, North et al (1996); 31, Schieck and Hobson (2000); 32, Schweitzer (2004); 33, Seip and Parker (1997);34, Siira-Pietikäinen et al (2001);35, Siira-Pietikäinen et al (2003); 36, Steventon et al (1998); 37, Sullivan and Sullivan (2001); 38, Sullivan et al (2000); 39, Vega (1993).…”
Section: Appendix Amentioning
confidence: 98%
“…For example, boreal forest birds are often hesitant to cross larger gaps in the forest (Bé lisle and Desrochers, 2002) and green-tree retention may therefore be more important on larger than smaller cuts. Several studies have also suggested higher rates of predation on both adults and eggs/nestlings in forests adjacent to clear-cuts (e.g., Sö derströ m et al, 1998;Rodriguez et al, 2001) but few studies have investigated if birds in neighbouring stands are affected by partial harvesting techniques (but see, e.g., Duguay et al, 2001).…”
Section: Introductionmentioning
confidence: 99%